On the Collaboration Uncapacitated Arc Routing Problem - Fernández, Elena; Fontana, Dario; Speranza, M. Grazia (Computers & operations research, 2016)
This paper introduces a new arc routing problem for the optimization of a collaboration scheme among carriers. This yields to the study of a profitable uncapacitated arc routing problem with multiple depots, where carriers collaborate to improve the profit gained. In the first model the goal is the maximization of the total profit of the coalition of carriers, independently of the individual profit of each carrier. Then, a lower bound on the individual profit of each carrier is included. This lower bound may represent the profit of the carrier in the case no collaboration is implemented. The models are formulated as integer linear programs and solved through a branch-and-cut algorithm. Theoretical results, concerning the computational complexity, the impact of collaboration on profit and a game theoretical perspective, are provided. The models are tested on a set of 971 instances generated from 118 benchmark instances for the Privatized Rural Postman Problem, with up to 102 vertices. All the 971 instances are solved to optimality within few seconds. •New arc routing problem introduced to handle a collaboration scheme among carriers.•We introduce two variants of the Collaboration Uncapacitated Arc Routing Problem.•Increasing collaboration will increase profits collecting.•We introduce a large set of benchmark instances.